2014
DOI: 10.1093/jac/dku129
|View full text |Cite
|
Sign up to set email alerts
|

ABCC2*1C and plasma tenofovir concentration are correlated to decreased glomerular filtration rate in patients receiving a tenofovir-containing antiretroviral regimen

Abstract: HIV-infected patients who carry ABCC2*1C genotype CC at position -24 or have high plasma tenofovir concentration are at risk of decreased glomerular filtration rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 24 publications
3
23
2
Order By: Relevance
“…The results from multivariate analysis showed that tenofovir plasma concentrations are associated with body weight, eGFR, concomitant use of a ritonavir-boosted protease inhibitor, and the polymorphism ABCC4 4131T ¡ G. A lower patient body weight was associated with higher tenofovir plasma concentrations in our study. This finding is consistent with the results from previous studies which demonstrated that body weight is one of the important predictors of tenofovir's pharmacokinetics (4,15,17).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results from multivariate analysis showed that tenofovir plasma concentrations are associated with body weight, eGFR, concomitant use of a ritonavir-boosted protease inhibitor, and the polymorphism ABCC4 4131T ¡ G. A lower patient body weight was associated with higher tenofovir plasma concentrations in our study. This finding is consistent with the results from previous studies which demonstrated that body weight is one of the important predictors of tenofovir's pharmacokinetics (4,15,17).…”
Section: Discussionsupporting
confidence: 93%
“…There is evidence of an association between tenofovir plasma concentrations and renal toxicity (4,6,7,14). A study by Rodríguez-Nóvoa et al has shown that patients with a tenofovir plasma concentration of more than 160 ng/ml at middose (10 to 14 h after the last dose) were at a 4.8 times higher risk of experiencing KTD than patients with a tenofovir plasma concentration below this cutoff value (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tenofovir penetrates in tubular cells by several tubular transporters. Polymorphisms in genes encoding for tubular transporters organic cationic transporter 1, multidrug resistant protein 2 (MRP-2) and 4 (MRP-4) were associated with increased tenofovir plasma concentrations and increased risk of KTD or of decrease in eGFR [8][9][10][11].…”
mentioning
confidence: 99%